Technical, Economical, and Marketing Analyses of Corotating Dual-Rotor Wind Turbines - Erturk, Ercan; Bulbul, Yasar; Guengoer, Ayseguel Sagkaya; Karagoz, Yasin; Pusat, Saban (WILEY-V C H VERLAG GMBH, 2024)
In this study, a comprehensive analysis is done on a dual rotor wind turbine (DRWT) in co-rotating arrangement. First, a co-rotating dual rotor is designed and its performance is analyzed by blade element momentum theory simulation. Later, the designed co-rotating DRWT is manufactured and then tested in the field by mounting the wind turbine on a truck. Running the truck steadily at different speeds while logging the performance parameters of the wind turbine, the power curve of the DRWT is obtained. Then, using the power curve of the co-rotating DRWT and the actual wind measurement data from & Ccedil;atalca Istanbul, the annual electricity generation of the designed turbine is calculated. The present techno-economic analysis states that the co-rotating DRWTs are more efficient compared to single rotor wind turbines (SRWTs), in accordance with the literature. Analyses show that with DRWT, around 22% higher power generation can be achieved. Additionally, the payback period for DRWT was found to be less than 1 year. The marketing strategy for introducing the product emphasizes identifying and targeting early adopters and influencers within the market. The present techno-economic analysis states that the co-rotating DRWTs are more efficient compared to SRWTs, in accordance with the literature. In this study, a comprehensive analysis is performed on a dual-rotor wind turbine (DRWT) in corotating arrangement. In the present techno-economic analysis, it is stated that the corotating DRWTs are more efficient (about 22%) compared to single-rotor wind turbines, in accordance with the literature.image (c) 2024 WILEY-VCH GmbH
Keywords: corotating dual rotors; economic analyses; renewable energies; wind energies; MODEL; Energy & Fuels